Method for evaluating service life of fluororubber static sealing material based on accelerated aging test
By using a combination of accelerated aging test and WLF equation in fluoroelastic static sealing materials, the problem of difficulty in accurately evaluating the life of fluoroelastic materials in the prior art is solved, and a more scientific life evaluation and higher accelerated aging efficiency are achieved.
Patent Information
- Application Number
- CN202411609142.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
The existing fluoro-rubber static sealing materials life evaluation methods are difficult to accurately consider the comprehensive impact of physical aging and chemical aging when evaluating fluoro-rubber materials, resulting in large deviations in the evaluation results.
Using a method based on accelerated aging test, compressing permanent deformation as a characterization index, accelerated aging test at four temperature points was carried out, and a function of test temperature and failure time of fluoroelastic static sealing material was established based on the WLF (Williams-Landel-Ferry) equation. , comprehensively consider physical aging and chemical aging to evaluate the life of the material.
This method can more scientifically evaluate the life of fluoroelastic static sealing material, improve accelerated aging efficiency, reduce deviations in evaluation results, and more accurately reflect the aging of the material under actual use conditions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluororubber static sealing materials, and specifically relates to a method for evaluating the life of fluororubber static sealing materials based on accelerated aging test. Background Art During long-term service, fluororubber static sealing materials and components will age under the influence of environmental factors such as heat and oxygen, resulting in their macroscopic performance being unable to meet the requirements of use. Premature damage to fluororubber static sealing materials will cause waste of resources and may also cause larger accidents. Therefore, the accelerated aging and life assessment of fluororubber static sealing materials have always been a hot topic of concern.
[0002] In terms of accelerated aging and life assessment methods for polymer materials, the methods currently used are mainly ISO2578:1993, GB / T 20028-2005, GB / T 7142-2002, GJB-92.1-86, GJB-92.2-86 and HG / T 3087-2001, etc. Among them, ISO 2578:1993, GB / T 20028-2005 and GB / T 7142-2002 are similar. The main contents of these methods are to carry out accelerated aging tests under no less than 3 temperature conditions, obtain the failure time under each temperature condition, and then process the data according to the Arrhenius law to evaluate the storage life of the material. The three methods of GJB-92.1-86, GJB-92.2-86 and HG / T 3087-2001 are similar in content. Accelerated aging tests are carried out under no less than four temperature conditions. The data processing method is to first calculate the logarithm of the performance retention rate-time (lnp-t α ) is used for linear regression to obtain the rate change constant K and other constants at different acceleration temperatures. Then, according to the Arrhenius law, a linear regression is performed on the logarithm of the rate change constant - the inverse of the test temperature (lnK-1 / T) to obtain the rate change constant at the storage temperature. This way, a performance degradation model is established to evaluate the storage life of the material.
[0003] Fluororubber has excellent chemical aging resistance due to its high CF bond energy, fluorine atom radius of about half the CC bond length, fluorine atoms can be tightly arranged around carbon atoms, molecular structure regularity is good, and tightly arranged fluorine atoms form a CC bond protection barrier. However, fluororubber has high polarity and strong intermolecular forces. When compressed, the molecular chains will have a certain orientation, the arrangement will be more compact and orderly, and the intermolecular forces will be further enhanced. After the compression load is removed, the stretched and slipped fluororubber molecular segments are difficult to overcome the intermolecular forces and return to their original positions, showing strong viscosity and prone to physical aging. The accelerated aging methods mentioned above are all based on data processing based on the Arrhenius equation describing chemical reactions. These methods will produce large deviations when used for life assessment of fluororubber static sealing materials that are prone to physical aging. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for evaluating the life of fluororubber static sealing materials based on accelerated aging tests. Compression permanent deformation is used as a characterization index, and accelerated aging tests are carried out at four temperature points. Physical aging and chemical aging are comprehensively considered, and a function of the test temperature and failure time of fluororubber static sealing materials is established based on the WLF (Williams-Landel-Ferry) equation to evaluate the life of fluororubber static sealing materials.
[0005] In order to solve the above technical problems, the present invention adopts the following technical scheme: first, the highest temperature of the accelerated aging test is determined, the temperature difference between adjacent temperatures is not less than 10°C, the remaining test temperature is determined, and according to the determined test temperature, a high-temperature compression permanent deformation test of fluororubber static sealing materials is carried out, and samples are taken regularly and the compression permanent deformation is measured; then, a polynomial regression analysis is performed with the logarithm of the aging time as the independent variable and the compression permanent deformation as the dependent variable to obtain the regression equation at each temperature point, and the failure time at each temperature point is calculated; finally, according to the failure time obtained at each accelerated aging test temperature, a function of the test temperature and failure time of the fluororubber static sealing material is established based on the WLF (Williams-Landel-Ferry) equation to evaluate the life of the fluororubber static sealing material and achieve the purpose of the present invention.
[0006] The present invention relates to a method for evaluating the life of a fluororubber static sealing material based on an accelerated aging test, which is characterized in that the method comprises the following steps: (1) Design of accelerated aging test temperature for fluororubber static sealing materials According to the relationship between fluororubber static sealing materials and temperature, four temperature points were selected to carry out accelerated aging tests on fluororubber static sealing materials, among which the highest temperature was set at 120°C; (2) Conducting accelerated aging tests at four temperature points on fluororubber static sealing materials According to the four selected test temperatures, the accelerated aging test of fluororubber static sealing materials was carried out, and samples were taken regularly to measure the compression permanent deformation; (3) Regression analysis of accelerated aging test results of fluororubber static sealing materials Taking the logarithm of aging time as the independent variable and compression set as the dependent variable, a polynomial regression analysis was performed on the accelerated aging test results of fluororubber static sealing materials to obtain the regression equation of fluororubber static sealing materials at various temperature points; based on the established failure critical value and the obtained regression equation of fluororubber static sealing materials, the failure time at various temperature points was calculated; (4) Determination of the performance degradation model of fluororubber static sealing materials at storage temperature The function of the test temperature and failure time of fluororubber static sealing materials is established according to the WLF equation. The equation is as follows:
[0007] Where: T is the test temperature, T r is the reference temperature, t and t r Temperature T and T r The failure time when the material properties reach the critical value, C 1 and C 2 is an empirical parameter.
[0008] Reversing the above formula, we get:
[0009] Select the lowest temperature in the accelerated aging test as the reference temperature T r , and its failure time is t r , through -1 / lg( t / t r ) vs 1 / ( T- T r ) was calculated by linear regression analysis. C 1 and C 2 The value of According to the WLF equation, we can get:
[0010] In the above formula, lg t rSubstituting into the polynomial regression equation at the reference temperature, the performance degradation model at the storage temperature is obtained; (5) Life evaluation of fluororubber static sealing materials at storage temperature The life of the fluororubber static sealing material at the storage temperature is calculated based on the obtained performance degradation model at the storage temperature and the set failure critical value.
[0011] Preferably, in the accelerated aging test temperature of the fluororubber static sealing material designed in step (1), the temperature difference between four adjacent temperature points is not less than 10°C.
[0012] Preferably, in the four-temperature point accelerated aging test of the fluororubber static sealing material in step (2), when sampling and measuring the permanent compression deformation of the fluororubber static sealing material sample, the compression device is first cooled to room temperature, and then the compression load is removed. After the sample recovers to a stable height at the standard laboratory temperature, its height is measured.
[0013] The present invention relates to a method for evaluating the life of a fluororubber static sealing material based on an accelerated aging test. By setting a reasonable accelerated aging test temperature, the aging mechanism of the fluororubber static sealing material under the accelerated aging condition and the room temperature service condition is kept consistent, and the method has a high accelerated aging efficiency. The present invention establishes a function of the test temperature and failure time of the fluororubber static sealing material based on the WLF (Williams-Landel-Ferry) equation to evaluate the life of the fluororubber static sealing material. The equation is based on the time-temperature equivalence principle, which is the basic principle for describing the viscoelasticity of polymers. Compared with other accelerated aging methods based on the Arrhenius equation for describing chemical reactions, the equation comprehensively considers physical aging and chemical aging, and can more scientifically evaluate the life of the fluororubber static sealing material. DETAILED DESCRIPTION
[0014] The present invention is further described below in conjunction with specific embodiments, but is not intended to limit the technical solutions of the present invention.
[0015] Example In this example, the compression permanent deformation of the fluororubber static sealing material reaches 30% as the critical failure value, and an accelerated aging test is carried out to establish a performance degradation model under the storage temperature of 23°C to evaluate its storage life. The specific steps are as follows: (1) Design of accelerated aging test temperature for fluororubber static sealing materials Accelerated aging test of fluororubber static sealing material was carried out at four temperature points. The designed maximum temperature of the accelerated aging test was 120°C, the temperature difference between adjacent temperatures was not less than 10°C, and the other three temperature points were 105°C, 95°C and 85°C respectively.
[0016] (2) Conducting accelerated aging tests at four temperature points on fluororubber static sealing materials According to the requirements of GB / T 7759.1, fluororubber static sealing material samples are prepared and placed in a heat aging test chamber using a compression device. According to the time points shown in Table 1, at four test temperature points, the heights of the fluororubber static sealing material samples are sampled and measured respectively, and then the compression permanent deformation is calculated based on the sample height. When sampling and measuring the compression permanent deformation of the fluororubber static sealing material samples, the compression device is first cooled to room temperature, and then the compression load is removed. After the sample recovers to a stable height at standard laboratory temperature, its height is measured. The compression permanent deformation results of the fluororubber static sealing material samples with accelerated aging at four temperature points are shown in Table 1.
[0017] Table 1 Accelerated aging test results of fluororubber static sealing material samples
[0018] (3) Regression analysis of accelerated aging test results of fluororubber static sealing materials Taking the logarithm of aging time as the independent variable and compression set as the dependent variable, polynomial regression analysis was performed on the test results at four temperature points to obtain the regression equations at each temperature point.
[0019] When the test temperature of fluororubber static sealing material is 85℃, the regression equation of accelerated aging test is: y=1.4403x3-1.8361x2+2.8954x+16.838 (1) When the test temperature of fluororubber static sealing material is 95℃, the regression equation of accelerated aging test is: y=0.8786x 3 -0.6615x 2 +3.4822x+18.177 (2) When the test temperature of fluororubber static sealing material is 105℃, the regression equation of accelerated aging test is: y=3.8151x 3 -8.8524x 2 +8.8114x+18.996 (3) When the test temperature of fluororubber static sealing material is 120℃, the regression equation of accelerated aging test is: y=2.1481x 3 -4.4509x 2 +7.7005x+20.156 (4) Where y is the compression set and x is the logarithm of the aging time.
[0020] The failure critical value was set at 30% compression set, and the failure time at each temperature point was calculated based on the obtained regression equations (1) to (4), as shown in Table 2.
[0021] Table 2 Failure time of fluororubber static sealing materials at various temperature points
[0022] (4) Determination of the performance degradation model of fluororubber static sealing materials at storage temperature The function of the test temperature and failure time of fluororubber static sealing material is established according to the WLF equation, which is shown in equation (5).
[0023] (5) Where: T is the test temperature, T r is the reference temperature, t and t r Temperature T and T r The failure time when the material properties reach the critical value, C 1 and C 2 is an empirical parameter.
[0024] By inverting equation (5), we can get: (6) The lowest temperature of 85°C in the accelerated aging test is selected as the reference temperature T r , its failure time t r is 166.6d, through -1 / lg( t / t r ) vs 1 / ( T- T r ) for linear regression analysis, the regression equation is: b = 53.49a + 0.26 (7) Where: b is -1 / lg( t / t r ), a is 1 / ( T- T r ).
[0025] According to the regression equation (7), C 1 The value of is 3.846, C 2 The value of is 205.722.
[0026] According to formula (5), we can get: (8) Substituting the storage temperature of 23°C into equation (8), we can obtain: (9) Substituting equation (9) into regression equation (1), the compression set performance degradation model at a storage temperature of 23°C is obtained as follows: y = 1.4403 (lgt-1.66) 3 -1.8361 (lgt-1.66) 2 + 2.8954 (lgt-1.66) + 16.838 (10) (5) Life evaluation of fluororubber static sealing materials at storage temperature According to the obtained decay model, taking the compression permanent deformation reaching 30% as the critical failure value, it can be obtained that the service life of fluororubber static sealing material at a storage temperature of 23°C is 7613d, that is, 20.8 years.
[0027] This embodiment establishes a function of test temperature and failure time based on the WLF equation, comprehensively considering the effects of physical aging and chemical aging on material properties. Compared with other accelerated aging methods based on the Arrhenius equation describing chemical reactions, it can more scientifically evaluate the life of fluororubber static sealing materials.
Claims
1. A method for evaluating the life of fluororubber static sealing materials based on accelerated aging test, characterized in that: The steps of this method are: (1) Design of accelerated aging test temperature for fluororubber static sealing materials According to the relationship between fluororubber static sealing materials and temperature, four temperature points were selected to carry out accelerated aging tests on fluororubber static sealing materials, among which the highest temperature was set at 120°C; (2) Conducting accelerated aging tests at four temperature points on fluororubber static sealing materials According to the four selected test temperatures, the accelerated aging test of fluororubber static sealing materials was carried out, and samples were taken regularly to measure the compression permanent deformation; (3) Regression analysis of accelerated aging test results of fluororubber static sealing materials Taking the logarithm of aging time as the independent variable and compression set as the dependent variable, a polynomial regression analysis was performed on the accelerated aging test results of fluororubber static sealing materials to obtain the regression equation of fluororubber static sealing materials at various temperature points; based on the established failure critical value and the obtained regression equation of fluororubber static sealing materials, the failure time at various temperature points was calculated; (4) Determination of the performance degradation model of fluororubber static sealing materials at storage temperature The function of the test temperature and failure time of fluororubber static sealing materials is established according to the WLF equation. The equation is as follows: Where: T is the test temperature, T r is the reference temperature, t and t r Temperature T and T r The failure time when the material properties reach the critical value, C 1 and C 2 is the empirical parameter. Invert the above formula to get: Select the lowest temperature in the accelerated aging test as the reference temperature T r , and its failure time is t r , through -1 / lg( t / t r ) vs 1 / ( T-T r ) was calculated by linear regression analysis. C 1 and C The value of 2; According to the WLF equation, we can get: In the above formula, lg t r Substituting into the polynomial regression equation at the reference temperature, the performance degradation model at the storage temperature is obtained; (5) Life evaluation of fluororubber static sealing materials at storage temperature The life of the fluororubber static sealing material at the storage temperature is calculated based on the obtained performance degradation model at the storage temperature and the set failure critical value.
2. The method for evaluating the life of a fluororubber static sealing material based on an accelerated aging test according to claim 1, characterized in that: In the step (1), the temperature difference between four adjacent temperature points in the accelerated aging test of fluororubber static sealing material is designed to be no less than 10°C.
3. The method for evaluating the life of fluororubber static sealing materials based on accelerated aging test according to claim 1, characterized in that: In the four-temperature point accelerated aging test of fluororubber static sealing material in step (2), when sampling and measuring the permanent deformation of the fluororubber static sealing material sample, the compression device is first cooled to room temperature, and then the compression load is removed. After the sample recovers to a stable height at standard laboratory temperature, its height is measured.
Citation Information
Cited By
Method and device for predicting aging life of chloroprene rubber lining
CN120213797A